2010
DOI: 10.1063/1.3526383
|View full text |Cite
|
Sign up to set email alerts
|

Systematic investigation of self-absorption and conversion efficiency of 6.7 nm extreme ultraviolet sources

Abstract: We have investigated the dependence of the spectral behavior and conversion efficiencies of rare-earth plasma extreme ultraviolet sources with peak emission at 6.7 nm on laser wavelength and the initial target density. The maximum conversion efficiency was 1.3% at a laser intensity of 1.6×1012 W/cm2 at an operating wavelength of 1064 nm, when self-absorption was reduced by use of a low initial density target. Moreover, the lower-density results in a narrower spectrum and therefore improved spectral purity. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…Recent theoretical work has proposed 6.76 nm as the optimum choice for the location of the reflectivity peak of EUV optics in a future lithography system based on the fact that the strongest lines observed in this region originate from Ag-and Pd-like ions [1][2][3]. Previous experimental work [4][5][6] has shown the spectral and in-band intensity dependence of Gd plasmas on laser wavelength, intensity and target composition and concentration. Spectra from pure Gd targets in the 6.7 nm region were shown to be optically thick, however, the opacity could be reduced by decreasing the Gd concentration or increasing the laser wavelength [5,6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent theoretical work has proposed 6.76 nm as the optimum choice for the location of the reflectivity peak of EUV optics in a future lithography system based on the fact that the strongest lines observed in this region originate from Ag-and Pd-like ions [1][2][3]. Previous experimental work [4][5][6] has shown the spectral and in-band intensity dependence of Gd plasmas on laser wavelength, intensity and target composition and concentration. Spectra from pure Gd targets in the 6.7 nm region were shown to be optically thick, however, the opacity could be reduced by decreasing the Gd concentration or increasing the laser wavelength [5,6].…”
mentioning
confidence: 99%
“…Previous experimental work [4][5][6] has shown the spectral and in-band intensity dependence of Gd plasmas on laser wavelength, intensity and target composition and concentration. Spectra from pure Gd targets in the 6.7 nm region were shown to be optically thick, however, the opacity could be reduced by decreasing the Gd concentration or increasing the laser wavelength [5,6]. As the ion stages involved in the 6.x nm radiation from Gd plasmas are higher than those of the 13.5 nm emitting ions of Sn plasmas, higher electron temperatures 4 are needed and thus higher laser power densities.…”
mentioning
confidence: 99%
“…These studies have shown that plasmas containing tin, where transitions of the type 4p 6 4d n -4p 5 4d n+1 + 4d n-1 4f overlap in ion stages from Sn 9+ -Sn 13+ to form an unresolved transition array (UTA) centered near 13.5 nm are the strongest emitters at this wavelength. To keep pace with Moore's law, research on shorter wavelength EUV sources has already begun [3][4][5][6][7][8].…”
mentioning
confidence: 99%
“…Recently, the suitability of Nd:yttrium-aluminum-garnet (Nd:YAG) laser-produced plasma (LPP) EUV sources based on Gd and Tb has been demonstrated for high power operation [3,7]. In order to achieve higher conversion efficiency (CE) from laser energy to EUV emission energy and spectral purity, the effects of optical thickness were evaluated by changing the laser wavelengths to change the plasma density and opacity [8]. The spectra of vacuum spark and laser plasma emission of Gd and Tb were first analyzed by Churilov and co-workers [4].…”
mentioning
confidence: 99%
“…12 However, while there are large numbers of papers reporting a Gd plasma generated by a YAG laser, all papers reported very broad spectra with a width larger than 1nm. 13,14 So, generating a 6.8 nm narrow peak in a Gd plasma by using a Nd:YAG laser is a challenging work.…”
Section: -2mentioning
confidence: 99%